Developing and validating anti-ADA2 single-chain antibodies coupled to alkaline phosphatase for diagnosing pleural tuberculosis - Skaldin, Maksym; Porcel, José M.; Lamminmäki, Urpo; Bielsa, Silvia; Zavialov, Andrey V. (Frontiers in Immunology, 2025)
IntroductionAdenosine deaminases ADA1 and ADA2 reduce adenosine concentrations, which regulate cellular immune responses to activation signals. It has been shown that ADA2 activity increases in the pleural fluid of patients with tuberculosis (TB).MethodsWe engineered recombinant scFv-AP antibodies using phage display technology to select high-affinity binders against ADA2. These were incorporated into a sandwich ELISA, allowing for the precise measurement of ADA2 levels in pleural fluid.ResultsThe assay was tested on pleural samples from 41 patients with TB and 47 with non-TB effusions, including those with malignancies and parapneumonic effusions. Results showed that ADA2 concentrations were significantly higher in patients with TB than in other groups, and the ADA2-based assay exhibited improved diagnostic specificity (91%) compared with total ADA testing (76%). A cutoff of 300 ng/mL for ADA2 yielded a sensitivity of 98% and a negative likelihood ratio of 0.03, effectively ruling out TB when the result was negative.DiscussionThe new ADA2 assay offers a simple, reliable, and more specific alternative for diagnosing pleural TB, with potential applications in other ADA2-related disorders.